Accessory Mental Foramen of the Mandible Found With Radiographic Images: A Case Report - Kabir, Md Humalun; Mallick, Parimal Chandra; Sarwar, AFM; Mohammad Rizvi, Hasan (Journal of Shaheed Suhrawardy Medical College, 2017)
The object of this study is to present a case of an accessory mental foramen. Detection of the position of mental foramen is important during surgical procedures in terms of achieving effective mandibular nerve blocks and avoiding injuries to the neurovascular bundles. A 64-year-o1d man visited us for taking treatment. Preoperative panoramic radiography and CT were conducted. A multi-section reconstructed sagittal image showed two mental foramina leading to the mandibular canal on the right side of the mandible, which were considered to be double mental foramina. Although no surgical procedure was planned, the patient was informed about the existence and importance of the anatomical variation with regard to the need for local anesthesia, diagnosis of periapical diseases, and the prevention of nerve damage during surgery in that area of his mandible J Shaheed Suhrawardy Med Coll, 2014; 6(2):90-92